2022
DOI: 10.3389/fped.2022.857436
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Limitations of Sirolimus in the Treatment of Vascular Anomalies—Insights From a Retrospective Case Series

Abstract: BackgroundDespite recent developments, the role of sirolimus in the heterogeneous spectrum of vascular anomalies is yet to be defined, in terms of indication, dosage, and therapy duration, recognizing both its potential and limitations.MethodsWe retrospectively analyzed 16 children with vascular anomalies treated with sirolimus in two pediatric centers between 2014 and 2020 [male: n = 7, the median age at diagnosis: 4.6 months (range, 0–281.4)]. In addition, repetitive volumetric analyses of the vascular anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
6
1
Order By: Relevance
“…This study conducted a retrospective analysis of the clinical effectiveness of sirolimus in pediatric patients with complex vascular anomalies, revealing a 60% rate of CR or PR. This rate is lower than the response rates reported in previous studies ( 2 , 3 , 6 8 ). The presence of selection bias in retrospective studies and potential ethnic differences should be considered.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This study conducted a retrospective analysis of the clinical effectiveness of sirolimus in pediatric patients with complex vascular anomalies, revealing a 60% rate of CR or PR. This rate is lower than the response rates reported in previous studies ( 2 , 3 , 6 8 ). The presence of selection bias in retrospective studies and potential ethnic differences should be considered.…”
Section: Discussioncontrasting
confidence: 75%
“…Sirolimus, a mammalian target of rapamycin (mTOR) inhibitor, has emerged as a promising therapeutic agent for refractory vascular anomalies ( 2 ). Sirolimus demonstrates potent immunosuppressive and anti-angiogenic properties, inhibiting the mTOR pathway, critical in angiogenesis and vascular endothelial cell proliferation ( 3 ). In preclinical studies, sirolimus has shown efficacy in inhibiting hemangioma growth by reducing endothelial cell proliferation, inducing apoptosis, and suppressing pro-angiogenic factors ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, low concentrations are not universally optimal for all cases. Karastaneva et al ( 17 ) reported that the most remarkable volume reductions were detected within the first 4–6 months of therapy. In all of our PR patients, the tumors had already reduced by >20% at 12 weeks, and a similar trend persisted at 24 and 52 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of sirolimus for the management of VM represented a paradigm shift in the approach to medical management . While sirolimus remains a critical part of the therapeutic armamentarium, data increasingly suggest that more precise targeting of gene variants may result in better outcomes . Because many of the genetic drivers of VM are shared with those found in cancers, most drugs under investigation have been borrowed from cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 While sirolimus remains a critical part of the therapeutic armamentarium, data increasingly suggest that more precise targeting of gene variants may result in better outcomes. 18 , 19 , 20 , 21 , 22 , 23 Because many of the genetic drivers of VM are shared with those found in cancers, most drugs under investigation have been borrowed from cancer treatments. Alpelisib (PIQRAY and Vijoice; Novartis), a drug that targets the PIK3CA gene, was approved in April 2022 by the US Food and Drug Administration for the treatment of a specific group of VM disorders: PIK3CA -Related Overgrowth Spectrum.…”
Section: Discussionmentioning
confidence: 99%